2014
DOI: 10.1177/0192513x13518210
|View full text |Cite
|
Sign up to set email alerts
|

Parental Nonstandard Work Schedules, Parent–Child Communication, and Adolescent Substance Use

Abstract: The purpose of this study was to examine the cumulative impact of parental nonstandard work schedules (NWS) on adolescent alcohol and cigarette use, with a focus on the mediating role of parent-child communication. Using the National Longitudinal Survey of Youth 1979 and its Child Supplement, our path analyses revealed that (a) parental NWS affected adolescent alcohol and cigarette use via the openness of parent-child communication rather than the frequency of parent-child communication and (b) the pattern and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 43 publications
(85 reference statements)
0
15
0
Order By: Relevance
“…Second, non-standard work may also compromise the quality of mother–child communication. Non-standard work hours are often associated with stressful working conditions, which may make excessive demands on mothers’ energy; consequently, even if mothers can squeeze in time to spend with their children, they will not necessarily have sufficient energy to engage in high-quality mother–child communication ( Presser, 2003 ; Kim et al, 2016 ). Gassman-Pines (2011) observed that night work or shift work can impair mothers’ physical and mental health and thus their ability to have healthy interactions with their children.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Second, non-standard work may also compromise the quality of mother–child communication. Non-standard work hours are often associated with stressful working conditions, which may make excessive demands on mothers’ energy; consequently, even if mothers can squeeze in time to spend with their children, they will not necessarily have sufficient energy to engage in high-quality mother–child communication ( Presser, 2003 ; Kim et al, 2016 ). Gassman-Pines (2011) observed that night work or shift work can impair mothers’ physical and mental health and thus their ability to have healthy interactions with their children.…”
Section: Introductionmentioning
confidence: 99%
“… Davalos et al (2005) determined that good parent–child communication enables parents to provide timely feedback to their children on their behavior, thereby improving that behavior and effectively reducing misbehavior and risky behavior. Kim et al (2016) also suggested that the openness of mother–child communication may negatively predict children’s risky behavior. Furthermore, good parent-child communication was observed to be associated with children’s higher self-esteem and well-being.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An important aspect of child development is socio-emotional and behavioral functioning, i.e., children's ability to monitor, evaluate, and modify their emotional reactions and social behaviors (Thompson and Meyer 2007). Poor socio-emotional functioning during childhood is associated with low educational attainment, poor labor market outcomes, antisocial behavior, substance abuse, and welfare dependency during adolescence and adulthood (Eisenberg et al 2001;Kim et al 2016;Schindler et al 2015). Inculcating emotion and behavior regulation in children is a costly and timeconsuming process, which requires a range of investments in the child.…”
Section: Introductionmentioning
confidence: 99%